74.3k views
0 votes
What is y when the equation is x^2 - 3xy -4y^2 =0

User Longblog
by
5.4k points

1 Answer

0 votes

Answer:

y = 1/8 (5 sqrt(x^2) - 3 x) or y = 1/8 (-3 x - 5 sqrt(x^2))

Explanation:

Solve for y:

-4 y^2 - 3 x y + x^2 = 0

Hint: | Multiply both sides by a term to make the coefficient of y^2 positive.

Multiply both sides by -1:

4 y^2 + 3 x y - x^2 = 0

Hint: | Using the quadratic formula, solve for y.

y = (-3 x ± 5 sqrt(x^2))/8:

Answer: y = 1/8 (5 sqrt(x^2) - 3 x) or y = 1/8 (-3 x - 5 sqrt(x^2))

User Gurbela
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.